2019
DOI: 10.1016/j.sleep.2018.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia symptoms and short sleep duration predict trajectory of mental health symptoms

Abstract: Objectives: Evaluate whether insomnia symptoms and short or long sleep duration, alone or in combination, are robustly associated with subsequent trajectory of mental health symptoms. Methods: Participants were 2,598 individuals (15-to-94 years of age) with elevated mental health symptoms at baseline (2013-14). Associations of baseline insomnia symptoms and sleep duration with two-year trajectory of mental health were estimated and adjusted for multiple potential confounders. Outcomes included recovery (well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 38 publications
1
34
0
Order By: Relevance
“…This can be partially attributed to the limited associations between inadequate sleep to the other health-related behaviours such that other health-related behaviours were no longer significantly associated with SRH after their adjustment. However, this finding also likely speaks to the importance of mental health and SRH given the consistent associations between sleep quality and mental disorders [47], and also the trajectory of mental health symptoms [48]. Others have also reported significant relationships between both short- and long- sleep duration and poor SRH, including in Canada [41].…”
Section: Discussionmentioning
confidence: 91%
“…This can be partially attributed to the limited associations between inadequate sleep to the other health-related behaviours such that other health-related behaviours were no longer significantly associated with SRH after their adjustment. However, this finding also likely speaks to the importance of mental health and SRH given the consistent associations between sleep quality and mental disorders [47], and also the trajectory of mental health symptoms [48]. Others have also reported significant relationships between both short- and long- sleep duration and poor SRH, including in Canada [41].…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have suggested that insomnia-related symptoms have the strongest effect on sickness absence when insomnia symptoms are coexisting with short sleep duration [40]. Extreme ends of the sleep duration distribution have also been associated with future sickness absence [41].…”
Section: Discussionmentioning
confidence: 99%
“…One recent study suggested that participants reported lower posttraumatic stress symptoms during COVID-19 outbreak when they had a better sleep 25 . Literature indicated that subjects who had insomnia or short sleep duration presented higher odds of developing chronic mental health symptoms 26 . Our study was consistent with previous ndings.…”
Section: Discussionmentioning
confidence: 99%
“…School children and adolescent, in particular, may feel more anxious because they had to learn in a completely different environment, which leads to sleep di culties 26 . Moreover, now the companies and schools reopened, convalescent psychiatric patients may need more time for adaption.…”
Section: Discussionmentioning
confidence: 99%